Experimental Study of Pulsed Discharge Underwater Shock-Related Properties in Pressurized Liquid Water. (23rd January 2018) - Bian, D. C.; Yan, D.; Zhao, J. C.; Niu, S. Q.
Abstract : Engineering background of hydraulic fracturing is applied to improve the permeability of unconventional gas wells, such as coal seams and shale gas wells, by a pulsed discharge mechanism. We studied the general relations between water shock wave properties (the maximum pressure, wave velocity, and energy conversion efficiency), the discharge voltage, and hydrostatic pressure during high-voltage pulsed discharge experiments in pressurized liquid water. The following observations were made: (1) when the discharge voltage increased from 7 kV to 13 kV, the maximum pressure increased from 12.6 MPa (hydrostatic pressure P H  = 12 MPa) to 40 MPa ( P H  = 6 MPa), wave velocity increased from 1418 m/s ( P H  = 12 MPa) to 1454 m/s ( P H  = 6 MPa), and energy conversion efficiency increased from 9% to 11%, and (2) when hydrostatic pressure increased from 0 MPa to 12 MPa, the maximum pressure and wave velocity augmented and then diminished slowly (the critical hydrostatic pressure occurs in the 3 to 6 MPa range), whereas the change of energy conversion efficiency was not obvious. Their properties are explained by the variation of electrical parameters during the pulsed discharge.